INFILTRATION OF WATER AND SALINITY IN LUVISSOLO OF THE BRAZILIAN SEMIARID CULTIVATED WITH DIFFERENT MANAGEMENT SYSTEMS - Holanda, Francisco Sandro Rodrigues; Araújo Filho, Renisson Neponuceno; Pedrotti, Alceu; Santos, Tiago Oliveira; Santos, Heide Vanessa Souza (REVISTA DE AGRICULTURA, 2017)
The objective of this study was to evaluate the basic infiltration rate (IB), the cumulative infiltration (CI) and electrical conductivity (EC) of saturated-paste extract, in a LUVISSOLO CRÔMICO cultivated under tillage systems such as conventional tillage (CT), the minimum tillage (MT) and no-tillage (NT), on crop rotation. The infiltration basic velocity (IB) andAccumulated infiltration(CI) were determined by the ring infiltrometer; EC by thesaturated-paste method and moisture by the gravimetric method. After two and a half years of field research, the infiltration rate and cumulative infiltration was greater in NT, followed by MT and CT.Higher water infiltration rates are related to the sites where conservation practices were adopted, improving soil structure.